Residential Status and Perceived Attitude towards Children with Non-Communicable Diseases in Ghana - Anarfi, J.; Yawson, A.; Abuosi, A.; Adzei, F.; Atobra, D.; Badasu, D.M. (My University, 2016)
Background: Non-Communicable Diseases (NCDs) have become quite prevalent worldwide. In Ghana as in other developing countries, NCDs are major public health concern. Even though modern health services have been sought by patients suffering from NCDs, poor attitude to those suffering from them exist in Ghanaian society because of traditional beliefs about the causes of such diseases. This paper examines parents and care givers’ perceived attitudes of Ghanaians towards NCDs among children. Methods: The study was conducted among 700 participants in three regions (Greater Accra, Ashanti and Volta) of Ghana in both rural and urban areas, using a quantitative research instrument. All the major ethnic groups of Ghana- Akan, Ewe, Ga-Dagme and Mole-Dagbani- were captured in the three regions. The dependent variables are: 1) perceived embarrassment of having a child with non-communicable disease, 2) discrimination from close associates and 3) difficulty of taking a child with non-communicable to social gatherings. The independent variable is residential status (rural and urban) and the control variables are socio-demographic characteristics of the respondents. Results: The findings indicate that the association between the background characteristics with perception of discrimination against families with children who have NCDs are significant according to the results of the Chi-Square test place of residence ( =10.678; p=0.005); level of education ( =19.389; p=0.036), and ethnic background ( =35.267; p=0.000). The results of the multinomial regression model show that those in rural areas have higher likelihood (92.0%) of perceiving that the family of a child with NCD will experience difficulty in going to social functions with the child compared with those in urban areas. Again, the rural dwellers are almost twice as likely (1.82%) to perceive that the family of a child with NCDs will feel embarrassed. Conclusion: Perceived attitude of society towards children with NCDs is generally poor in the study population. Perceived discrimination against families of such children suggests that the children may not be availed for treatment even as it is indicated that the parents/care givers will have difficulty in taking them out to public places. Rural residents have higher likelihood of such attitudes Health policies need to address such attitudes in Ghanaian society and must target rural residents while not neglecting urban dwellers.
Keywords: Non-Communicable Diseases; Children; Attitude; Rural; Urban; Ghana